Performance Analysis of Circular 8-QAM Constellation with MMSE Equalizer for OFDM System Using USRP - Taufiqurrahman, Muh. Alfan; Astawa, I Gede Puja; Sudarsono, Amang (Politeknik Elektronika Negeri Surabaya (PENS), 2016)
Bandwidth is very important in communication system, and it is a limited resource. In order to save the limited bandwidth resource, high order M-ary modulation is widely employed in modern communication and broadcasting systems. In Orthogonal Frequency Division Multiplexing (OFDM), fading environment lead to a loss of orthogonality between the subcarriers. In this paper, we present the performance analysis of circular 8-Quadrature Ampilutude Modulation (QAM) constellation for Orthogonal Frequency Division Multiplexing (OFDM) system. We also combine the system with Minimum Mean Square Error (MMSE) equalizer to mitigate the effect of Inter Symbol Interference (ISI). Then, all of this system is implemented practically using Universal Software Radio Peripheral (USRP). The performance of circular 8-QAM and MMSE equalizer is evaluated by comparing with other 8-QAM modulation models such as circular-Zero Forcing (ZF), star-ZF, Square-ZF, Star-MMSE, and Square-MMSE. The performance of circular 8-QAM with MMSE equalizer isÂ better than the other combinations. Bit Error Rate (BER) graph shows that the performance of circular-MMSE is better than star-MMSE. The performance improvement using circular-MMSE is about 1.6%. The performance will decrease when the distance is increased. The performance of this system is greatly affected by the distance between transmitter and receiver.